Health risk behaviors in adolescents and young adults with special health care needs. Issue 1 (February 2015) - Pilapil, Mariecel; DeLaet, David
<x xml:space="preserve">Abstract</x> Purpose of review Adolescents and young adults with special health care needs (SHCN) are uniquely vulnerable to health risk behaviors including smoking, alcohol and illicit drug use, and sexual risk-taking. Their likelihood of experiencing adverse health outcomes because of these behaviors may be beyond that experienced by their healthier peer group. Pediatric providers are responsible for appropriately counseling these patients about healthy lifestyles. This review provides some background regarding these health risks among adolescents and young adults with SHCN with particular focus on three populations: childhood cancer survivors, congenital heart disease patients, and those with intellectual disability. Recent findings Young adults and adolescents with chronic medical conditions are as likely – and perhaps more likely – to engage in health risk behaviors. However, these behaviors are not fully addressed by primary care providers. Summary Pediatric providers are encouraged to ask adolescents and young adults with SHCN about their understanding of, and engagement in, health risk behaviors. A multidisciplinary approach to encourage a healthy lifestyle within this population may have significant health benefits.